Recovery of inclusion body protein in Escherichia coli: Effects of solubilization methods and process condition - Chew, Few Ne; N. H. Z., Abidin; N. H.M, Yusof; N.M, Rafi; Chua, Gek Kee (IOP Publishing, 2019)
Inclusion bodies (IBs) are produced in Escherichia coli cells and solubilization process is required to recover desired protein in bioactive form. Conventional and mild solubilization methods were applied for IBs solubilization and the performances were influenced by respective process condition. Therefore, it is the objective of current work to investigate the effects of solubilization methods on the recovery of soluble enhanced green fluorescent protein (EGFP) from IBs by using urea, alkyl alcohol and freeze thaw method. The present study indicates urea concentration, incubation temperature, type of alcohol and its concentration, freezing duration and freeze thaw cycles influenced the yield and purity of solubilized EGFP. Conventional method using 8 M of urea with incubation temperature of 60°C achieved the highest yield (61%) and purity (10%). Mild IBs solubilization with 6 M of n-butanol and 2 M of urea has solubilized IBs with a yield of 45% and purity of 22%. By freezing and thawing the IBs suspension in 2 M of urea, the yield (66%) and purity (9%) of solubilized EGFP were comparable to that of 8 M of urea in buffer. Hence, mild solubilization using the alkyl alcohol or freeze thaw method is applicable for IBs solubilization.